Psycholinguistic and Cognitive Characteristics of Simultaneous Interpreting: Mechanisms, Models, and Implications for Training - Joniqulov Abdullo Ziyodullo Ogli (Goodwood Publishing, 2026)
Purpose: This study investigates the psycholinguistic and cognitive characteristics of simultaneous interpreting (SI), emphasizing working memory, selective and sustained attention, bilingual language control, incremental processing, and anticipation. It also explores how these mechanisms inform interpreter training program design.Methodology: A systematic analytical review synthesized theoretical models and empirical findings from cognitive psychology, psycholinguistics, bilingualism research, and interpretation studies. Key frameworks include Effort Model, multicomponent working memory model, and dual-process theories of cognition. Results: SI requires the parallel execution of speech perception, semantic decoding, conceptual reformulation, and target language production under strict temporal constraints. Interpreter performance depends on a dynamic balance among four cognitive efforts, listening and analysis, production, memory, and coordination, within fixed processing capacities. Conclusions: Expertise in SI emerges from systematic cognitive development rather than innate talent. Effective training should develop working memory, attentional control, inhibitory function, and anticipatory processing alongside linguistic proficiency using techniques such as shadowing, paraphrasing, and dual-task exercises.Limitations: The study is theoretical and relies on existing literature, primarily on Western European and North American language pairs, limiting generalizability to other pairs, such as Uzbek-English.Contributions: This article consolidates psycholinguistic and cognitive insights into a coherent framework, offering evidence-based implications for interpreter pedagogy and training program design.